The potential of enzymatic hydrolysis with HS-SPME-GC×GC-ToFMS for the study of volatile signature of grapes - Fonseca, Daniela (2025)
This works focuses on developing an optimized methodology for analyzing free and bound volatile compounds in grapes using enzymatic hydrolysis with AR2000 enzyme and HS-SPME-GC × GC-ToFMS. To achieve this purpose, a previous optimization step of enzymatic hydrolysis was implemented and optimal conditions for enzymatic hydrolysis were established using 50 mg of AR2000 enzyme at 35 ◦C for 24 h, while the best extraction conditions were found to be 40 min at 60 ◦C. Applying this methodology to clones of Moreto grapes from harvest of 2022 and 2023, it was possible to identify and semi-quantify sixty volatile compounds, with more compounds identifiable in 2022 than in 2023. The results also showed the influence of crop year and genetic intravariability